(untitled) - Boyd, Cindy J. (New York, 1999)
This book includes 13 chapters: Chapter 1: Problem solving, numbers, and algebra; Chapter 2: Statistics: graphing data; Chapter 3: Adding and subtracting decimals; Chapter 4: Multiplying and dividing decimals; Chapter 5: Using number patterns, fractions, and ratios; Chapter 6: Adding and subtracting fractions; Chapter 7: Multiplying and dividing fractions; Chapter 8: Exploring ratio, proportion, and percent; Chapter 9: Geometry: investigating patterns; Chapter 10: Geometry: understanding area and volume; Chapter 11: Algebra: investigating integers; Chapter 12: Algebra: exploring equations: Chapter 13: Using probability.
Keywords: Mathematics,Toán học; Study and teaching ( Elementary ),Học và giảng dạy ( Tiểu học )